2023
DOI: 10.1371/journal.pone.0282844
|View full text |Cite
|
Sign up to set email alerts
|

The indelible toll of enteric pathogens: Prevalence, clinical characterization, and seasonal trends in patients with acute community-acquired diarrhea in disenfranchised communities

Abstract: Background There is little information on the epidemiology of enteric pathogens in Lebanon, a low- and middle-income country that suffers from a myriad of public health challenges. To address this knowledge gap, we aimed to assess the prevalence of enteric pathogens, identify risk factors and seasonal variations, and describe associations between pathogens among diarrheic patients in the Lebanese community. Methodology and principal findings A multicenter cross-sectional community-based study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
4
4
0
Order By: Relevance
“…The primary aim of this study was to assess the utility of implementing the multiplex PCR assay for the identification of enteric pathogens in Lebanon especially those traditionally challenging to identify using conventional diagnostic methods. Our results are consistent with the work of Osman et al, who utilized the BioFire FilmArray [ 26 ]. This alignment strengthens the validity of our findings, highlighting the effectiveness of multiplex PCR for comprehensive pathogen detection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The primary aim of this study was to assess the utility of implementing the multiplex PCR assay for the identification of enteric pathogens in Lebanon especially those traditionally challenging to identify using conventional diagnostic methods. Our results are consistent with the work of Osman et al, who utilized the BioFire FilmArray [ 26 ]. This alignment strengthens the validity of our findings, highlighting the effectiveness of multiplex PCR for comprehensive pathogen detection.…”
Section: Discussionsupporting
confidence: 93%
“…In our current study, implementation of multiplex PCR as a stool diagnostic test revealed a high positivity rate of 71% (192/271) for enteropathogens, 46% (88/192) as single infections and 54% (104/192) as mixed infections. Our study is consistent with previous study conducted in Lebanon which strengthens the validity of our findings, demonstrating the effectiveness of multiplex PCR for comprehensive pathogen detection [ 26 ]. A total of 29% of our samples (79/271) were negative; this could have been attributed to a non-infectious origin or immediate start of empiric treatment prior to sample collection and other idiopathic causes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As for viruses, rotavirus (27.5%) and norovirus (7.5%) were the primary viral causes of diarrhea. [12] The findings in the present study, as well as the trends seen in recent years and in the literature, all point to an increase in infectious diarrheal cases caused by pathogens that thrive in poor living conditions. This is the main reason why diarrheal illness is more prevalent in developing countries, where poor knowledge about sanitation and hygiene, contamination of water with fecal material, the use of left-over food, and a low nutritional and public health status all contribute to propagation of diarrheal disease.…”
Section: Discussionsupporting
confidence: 79%
“…This lack of clarity is compounded by the limited epidemiological data for Shigella in Lebanon due to the lack of robust and sustainable epidemiological surveillance programmes and the challenges faced by most clinical laboratories in the identification of Shigella and its differentiation from enteroinvasive Escherichia coli (EIEC) [12, 13]. A study recently conducted in two Lebanese tertiary healthcare settings showed that EIEC and Shigella accounted for 18.9 % of the enteric pathogens isolated from patients with acute community-acquired diarrhoea [12]. Lebanon is currently grappling with calamitous challenges to its infrastructure and political stability, together with pollution, associated with a severe economic collapse that resulted in an acute devaluation of its currency by more than 95 % and shortages of imported goods, limiting the availability and increasing the prices of essential goods, with an impact on public health, including critically important antimicrobial drugs (CIAs) [14].…”
Section: Introductionmentioning
confidence: 99%